2016
DOI: 10.1371/journal.pone.0164232
|View full text |Cite
|
Sign up to set email alerts
|

Throat Swabs and Sputum Culture as Predictors of P. aeruginosa or S. aureus Lung Colonization in Adult Cystic Fibrosis Patients

Abstract: BackgroundDue to frequent infections in cystic fibrosis (CF) patients, repeated respiratory cultures are obtained to inform treatment. When patients are unable to expectorate sputum, clinicians obtain throat swabs as a surrogate for lower respiratory cultures. There is no clear data in adult subjects demonstrating the adequacy of throat swabs as a surrogate for sputum or BAL. Our study was designed to determine the utility of throat swabs in identifying lung colonization with common organisms in adults with CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…Seidler et al . reported that in expectorating adults (n = 20), OP swab and sputum cultures both had a PPV of 1.00 for detecting P. aeruginosa and NPV of 0.50 and 0.60, respectively 39 . In this work, 28 putative volatile biomarkers were selected across all our models for the identification of P. aeruginosa in BAL fluid samples yielding a PPV range of 0.25–0.81 and an NPV range of 0.56–0.92.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seidler et al . reported that in expectorating adults (n = 20), OP swab and sputum cultures both had a PPV of 1.00 for detecting P. aeruginosa and NPV of 0.50 and 0.60, respectively 39 . In this work, 28 putative volatile biomarkers were selected across all our models for the identification of P. aeruginosa in BAL fluid samples yielding a PPV range of 0.25–0.81 and an NPV range of 0.56–0.92.…”
Section: Discussionmentioning
confidence: 99%
“…Seidler et al . reported an NPV of 1.00 for detecting S. aureus in OP swab and sputum cultures versus BAL fluid and a PPV of 0.41 for OP swab and 0.57 for sputum versus BAL fluid 39 . Neericnx et al .…”
Section: Discussionmentioning
confidence: 99%
“…Properly defining coinfection may also be influenced by the sampling methods used, particularly in young children, who often do not expectorate. Some studies indicate that both sputum and oropharyngeal swab cultures can, in some contexts and for specific organisms, reflect lower airway microbiology identified by bronchoalveolar lavage (BAL)45 or direct sampling of mucous plugs by protected brush (PB) sampling,46 while other studies found poor such correlations. For example, Seidler and colleagues found that while the positive predictive value of both sputum and throat swabs for identifying P. aeruginosa was 100%, in comparison with BAL, the positive predictive values of these two sample types for S. aureus were only 57% and 41%, respectively 45.…”
Section: Epidemiology Of P Aeruginosa and S Aureus Infections In Cymentioning
confidence: 99%
“…There are several studies looking at routine throat swabs for the isolation of pathogens in CF mainly in the paediatric populations. A recent study looked at throat swabs as a marker of lower‐airway Pseudomonas colonization . This study showed that both sputum and throat swab were 100% sensitive in predicting BAL Pseudomonas, whereas the negative predictive value of a throat swab was only 50%.…”
Section: Discussionmentioning
confidence: 98%